Possible Advantages of S53P4 Bioactive Glass in the Treatment of Septic Osteoarthritis of the First Metatarsophalangeal Joint in the Diabetic Foot - Kastrin, Matevž; Urbančič Rovan, Vilma; Frangež, Igor (Journal of clinical medicine, 2021)
Biomechanically, the great toe with its metatarsophalangeal (MTP) joint plays a key role in standing and walking, making the first MTP joint one of the main predilection sites for ulcer formation, and consequently for bone and joint infection and even amputation. If conservative treatment fails, the main goal of surgery is to remove all infected tissue and preserve the first ray. To improve surgical outcomes, development of new biomaterials like Bioactive Glass S53P4 has begun. Bioactive Glass is useful because of its antibacterial properties; furthermore, its osteostimulative and osteoconductive qualities make the bone substitute particularly suitable as a bone defect filler for the treatment of osteomyelitis. The aim of our retrospective observational study was to compare the outcomes following ulcerectomy with segmental resection of the infected joint and bone and temporary stabilization with an external fixator, both with and without added Bioactive Glass. A comparison of added Bioactive Glass with the traditional surgical treatment in septic osteoarthritis of the first MTP joint showed Bioactive Glass to be effective. During a one-year follow-up, patients with Bioactive Glass required no additional antibiotic therapy or surgical intervention. Bioactive Glass, when applied to the diabetic foot, showed itself to be a safe bone substitute biomaterial.